The McDonaldization of society - Ritzer, George, 1940- (Sage, 2015)
"The McDonaldization of Society is George Ritzer's seminal work of critical sociology that links classical sociological theory to many aspects of contemporary life in a globalized world--Max Weber's rationalization thesis updated and applied to the late 20th and early 21st century. Where Weber focused on bureaucracies as the "iron cages" of rationalization in his time, the central premise of McDonaldization is that the fast food restaurant has become the model for the rationalization process today. The book examines ways in which fast food businesses have created a system of operation based on efficiency, calculability, predictability, and control; and how the same principles have been applied to other settings and contexts as diverse as motel chains, "big box" stores, churches, child care centers, college rankings, health care providers, the Internet, and political participation. The author also looks at attempts to resist and reverse the effects of McDonalization. "McDonalization" has become part of the lexicon of contemporary sociological theory, and the book has been widely adopted and read for over twenty years by hundreds of thousands of students in a wide variety of courses, including many courses created specifically to explore the phenomena of McDonaldization."--Resumé vydavatele
Keywords: McDonald's Corporation; globální společnost; konzumní společnost; životní styl -- Spojené státy americké; rychloobslužné restaurace -- Spojené státy americké; management -- sociální aspekty; global society; consumer society; life style -- United States; fast food restaurants -- United States; management -- social aspects; Spojené státy americké -- sociální poměry; United States -- social conditions; studie; studies